Autoplagiarism and Its Impact on Maritime Occupational Health - Jimy Fran (The Indonesian Journal of Community and Occupational Medicine, 2026)
Introduction: Scientific integrity violations in maritime occupational health research have escalated alarmingly, yet remain systematicallyunderexamined. This study aimed to map patterns, triggering factors, and ethical implications of autoplagiarism within maritime workerresearch publications.Method: A narrative review was conducted across PubMed, Scopus, Web of Science, and Google Scholar (2015–2025), yielding eightsynthesized articles.Results: Three dominant autoplagiarism manifestations were identified: redundant publication, text recycling, and salami publication, drivenby scarce primary data accessibility, absence of domain-specific publication ethics guidelines, publish-or-perish pressures, and homogeneousresearcher communities undermining peer-review.Conclusions: These practices systematically distort the evidence base informing IMO and ILO maritime health policies while impedinggenuine intervention innovation for globally vulnerable seafaring populations. Comprehensive reform across three levels is urgently warranted:mandatory prior publication disclosure by journal editors, ethics literacy institutionalization in postgraduate curricula, and establishment ofan open maritime research data registry to structurally eliminate dataset recycling incentives.